Pluronic F-68 improves root growth of recalcitrant rice cultivar through enhanced auxin biosynthesis - Kok, Andrew De Xian; Ong-Abdullah, Janna; Shen-Yee Kong, Amanda; Sekeli, Rogayah; Wee, Chien Yeong; Erin Lim, Swee Hua; Cheng, Wan Hee; Loh, Jiun Yan; Lai, Kok Song (Penerbit Universiti Sains Malaysia, 2025)
In plants, roots play a vital role in crop performance and yield that impact the agricultural productivity. Pluronic F-68 (PF-68) is a type of non-ionic surfactant that is typically utilised as a plant growth additive. There is a lack of studies on the impact of PF-68 on root growth. This work aims to assess the impacts of PF-68 on recalcitrant MR 219 rice root growth. Supplementation of 0.04% PF-68 enhanced the length (18.50%) and number of roots (15.87%) of MR 219 rice. The PF-68-treated MR 219 rice also showed a significant increment in sugar accumulation (1.73 mg/mL) and glutamate synthase activity (0.88 µmol/g protein). Consistent with the root growth enhancement, MR 219 rice supplemented with PF-68 recorded an increase in transcription levels of Indole-3-Acetic Acid 23 (OsIAA23) (1.84-folds) and WUSCHEL-Related Homeobox 11 (OsWOX11) (2.00-folds). Moreover, the PF-68-treated MR 219 rice also exhibited an enhancement of indole acetic acid (IAA) concentrations (27.33 ng/g FW), further suggesting its role in auxin biosynthesis. Taken together, our study revealed that the introduction of PF-68 enhanced the root growth of MR 219 rice through improved sugar accumulation, glutamate synthase activity and auxin biosynthesis.